Uji Kualitas Citra Pesawat CT-Scan Menggunakan Phantom ACR (American College of Radiology) di Instalasi Radiologi Rumah Sakit Universitas Andalas - Machmudah; Muttaqin, Afdhal; Oktavia, Amel (Jurnal Fisika Unand, 2025)
This research aims to obtain optimal image quality by ensuring that the CT Number measurement results do not exceed the limits set using Phantom ACR in the Radiology Installation of Andalas University Hospital with a Philips brand CT-Scan 64 Slice machine, because CT-Scan image quality testing is an important step to ensure optimal performance of radiology diagnostic tools and guarantee the accuracy of examination results. This research uses an experimental method with an evaluation consisting of four modules: Module 1 (CT Number accuracy) shows that the values for Polyethylene, Air, Acrylic and Water materials are within the tolerance limits of BAPETEN No. 2 of 2022 is ±5 HU, while the bone material does not meet the criteria, which indicates the need for additional calibration for high density materials. Module 2 (low contrast resolution), CNR (Contrast to Noise Ratio) value of 2.91 shows clear contrast between structures with low noise, meets BAPETEN standard No. 2 of 2022. Module 3 (CT Number uniformity), uniformity testing produces standard deviation values below the limit ≤ 2 HU, indicating good uniformity in the center and edges of the image, making it reliable for clinical applications. Module 4 (spatial resolution with high contrast), the CT-Scan system shows a resolution of 6 lp/cm, in accordance with the minimum limit set by BAPETEN No. 2 of 2022. Overall, this research shows that the CT-Scan system can produce images that meet BAPETEN standards No. 2 of 2022 for good image quality and can be applied in clinical practice, but for bone material it does not meet the criteria with an average value of 838.1 ± 17.4 HU.